TRADISI PERINGATAN HAUL DALAM PENDEKATAN SOSIOLOGI PENGETAHUAN PETER L. BERGER - Hanif, Abdulloh (Dialogia: Jurnal Studi Islam dan Sosial, 2015)
Abstract: Haul is a tradition typical of Muslims in Indonesia. Although as a term, can be likened to haul in the tradition of pilgrimage of Muslims in general, but in Indonesia haul have different shapes and implementation in practice with the pilgrimage. This can be seen clearly as an institutionalized social activity. Meaning of pilgrimage as a reminder of death eventually not be the main objective in the implementation of the haul, although religious motives still underlie the practice. However haul relfeksi has become a kind of history, not just in view of the transience of human life, but rather the development of the vision and mission of human life further they get from the reflection of history celebrated figures. Making of history eventually become important to observe. History is not just a stretch of the past, present, and future, but, in the context of haul, history is closely related to building public awareness about the celebrated figures, either directly or through stories or media. Building awareness is what allows every individual who commemorate haul will internalize the objects of consciousness different from the historical reflection, although figures are presented objectively observed through individuals close to and understand objectively as himself. It is at least able to prove that religion is very closely linked to community activities.Keywords: Haul, Peter L. Berger, Sosiologi Pengetahuan dan Refleksi Sejarah.